Java in a nutshell - Evans, Benjamin J.; Flanagan, David (Beijing, China ; Boston, Massachusetts : O'Reilly Media, Inc., 2019)
"This updated edition of Java in a Nutshell not only helps experienced Java programmers get the most out of Java versions 9 through 11, its also a learning path for new developers. Chock full of examples that demonstrate how to take complete advantage of modern Java APIs and development best practices, this thoroughly revised book includes new material on Java Concurrency Utilities. The books first section provides a fast-paced, no-fluff introduction to the Java programming language and the core runtime aspects of the Java platform. The second section is a reference to core concepts and APIs that explains how to perform real programming work in the Java environment. Get up to speed on language details, including Java 9-11 changes Learn object-oriented programming, using basic Java syntax Explore generics, enumerations, annotations, and lambda expressions Understand basic techniques used in object-oriented design Examine concurrency and memory, and how theyre intertwined Work with Java collections and handle common data formats Delve into Javas latest I/O APIs, including asynchronous channels Use Nashorn to execute JavaScript on the Java Virtual Machine Become familiar with development tools in OpenJDK."--Back cover.
Introduction to the Java environment -- Java syntax from the ground up -- Object-oriented programming in Java -- The Java type system -- Introduction to object-oriented design in Java -- Java's approach to memory and concurrency -- Programming and documentation conventions -- Working with Java collections -- Handling common data formats -- File handlin and I/O -- Classloading, reflection, and method handles -- Java platform modules -- Platform tools.
David Flanagan appears as author on previous editions.
"Covers Java 11"--Cover.
Includes index.
CSE
Keywords: Java (Computer program language).; Web servers; Object-oriented programming (Computer science).; Computer science; Java (Computer program language); Object-oriented programming (Computer science); Web servers